Use of membrane technology and resins for the separation and purification of polyphenols purple tree tomato (Solanum betaceum Cav) - Beltrán, Elena; Pallet, Dominique; Vera, Edwin; Ruales, Jenny (Enfoque UTE, 2016)
The polyphenols fractionation of mesocarp juices, placenta and purple tree tomato peel using the pore size of the membrane as a means of selection was performed using micro and ultrafiltration tangential; tests made with HPLC showed that fractionation of phenolic compounds was not performed. The processes of concentration of the clarified juices of placenta and tree tomato peel by reverse osmosis obtained a volumetric concentration factor of 2 and 2.2 respectively. The polyphenol concentration increased by 1.5 times for placenta and 2.4 times for peel and antioxidant capacity increased by 2.4 times for both juices. The anthocyanins of placenta increased by 2.6 times. The use of the resin XA 5071 FG concentrated phenolic compounds with an increase of antioxidant capacity in a range between 4 and 5.5, and anthocyanins concentration was increased 1.8 times in the placenta juice. In conclusion the process of polyphenols concentration of tree tomato was more efficient using the resin XA 5071 FG than the reverse osmosis applied in this research.